2008
DOI: 10.4103/0971-9784.38446
|View full text |Cite
|
Sign up to set email alerts
|

Early goal-directed therapy in moderate to high-risk cardiac surgery patients

Abstract: Early goal-directed therapy is a term used to describe the guidance of intravenous fluid and vasopressor/inotropic therapy by using cardiac output or similar parameters in the immediate post-cardiopulmonary bypass in cardiac surgery patients. Early recognition and therapy during this period may result in better outcome. In keeping with this aim in the cardiac surgery patients, we conducted the present study. The study included 30 patients of both sexes, with EuroSCORE >or=3 undergoing coronary artery bypass su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(123 citation statements)
references
References 0 publications
4
107
0
12
Order By: Relevance
“…Cecconi et al showed improved outcomes in 40 patients receiving regional anesthesia for hip arthroplasty [33]. Kapoor et al showed a decrease in the duration of mechanical ventilation, ICU LOS, and hospital LOS in patients undergoing cardiac surgery [34]. Targeting a PPV <10% has been shown to improve postoperative outcomes and reduce length of intensive care and hospital stay in high-risk surgical patients [35].…”
Section: Does Gdft Improve Outcomes?mentioning
confidence: 99%
“…Cecconi et al showed improved outcomes in 40 patients receiving regional anesthesia for hip arthroplasty [33]. Kapoor et al showed a decrease in the duration of mechanical ventilation, ICU LOS, and hospital LOS in patients undergoing cardiac surgery [34]. Targeting a PPV <10% has been shown to improve postoperative outcomes and reduce length of intensive care and hospital stay in high-risk surgical patients [35].…”
Section: Does Gdft Improve Outcomes?mentioning
confidence: 99%
“…An increase in intra-thoracic pressure generates an isovolaemic increase in RAP, which decreases dVR and decreases VR. Some of these variables have been used in GDT protocols (37,38). A systolic pressure or a pulse pressure variation of 13% or more in septic patients breathing with a tidal volume of 8 mL kg -1 is highly sensitive and specific for preload responsiveness (39).…”
Section: For Preloadmentioning
confidence: 99%
“…Also there are data showing that keeping the oxygen extraction ratio, calculated from arterial and central venous oxygen saturation, below 27% resulted in less postoperative organ dysfunction and reduced hospital stay of high-risk surgical patients (16). However, early GDT including the maintenance of ScvO 2 higher than 70% in moderate and high risk cardiac surgical patients was found to be inconclusive regarding benefits (39). In a recent observational study in surgical patients, even higher levels of ScvO 2 have been reported (84.7±8.3%) (40).…”
Section: Assessing and Treating Hypovolemia Induced Oxygen Debtmentioning
confidence: 99%